Artemisinins target GABAA receptor signaling and impair α cell identity. - Li, J; Casteels, T; Frogne, T; Ingvorsen, C; Honoré, C; Courtney, M; Huber, K; Schmitner, N; Kimmel, R; Romanov, R; Sturtzel, C; Lardeau, C; et al. (Elsevier, 2016)
Type 1 diabetes is characterized by the destruction of pancreatic beta cells, and generating new insulin-producing cells from other cell types is a major aim of regenerative medicine. One promising approach is transdifferentiation of developmentally related pancreatic cell types including glucagon-producing alpha cells. In a genetic model, loss of the master regulatory transcription factor Arx is sufficient to induce the conversion of alpha cells to functional betalike cells. Here we identify artemisinins as small molecules that functionally repress Arx by causing its translocation to the cytoplasm. We show that the protein gephyrin is the mammalian target of these antimalarial drugs, and that the mechanism of action of these molecules depends on the enhancement of GABAA receptor signaling. Our results in zebrafish, rodents and primary human pancreatic islets identify gephyrin as a druggable target for the regeneration of pancreatic beta cell mass from alpha cells.